The low-FODMAP recipe book : relieve symptoms of IBS, Crohn's Disease and other gut disorders in 4 to 6 weeks - Whigham, Lucy (Aster, 2017)
"In a landmark study, Australian researchers asked patients with IBS to remove FODMAPs from their diet. They found 74 per cent reported that their symptoms, such as bloating, abdominal pain, gas, excessive burping, diarrhoea and constipation, had improved dramatically. The findings so impressed gastroenterologists at King's College London that they adapted the diet for the UK and many British patients are now on the Low FODMAPT diet. At first glance, the Low FODMAPT diet may appear daunting, as it involves cutting out all five families of fermentable carbohydrates: Fructans (wheat, rye, onions, garlic and various other grains and vegetables), Galacto oligosaccharides (beans and pulses), Polyols (certain fruit, sugar-free gum and mints), Fructose (various fruits, honey and agave nectar) and Lactose (animal milks, yogurts and some cheeses). However, this book gives practical guidance on how to follow the regime while ensuring a balanced, nutrient-rich diet, transforming the Low FODMAPT diet from a seeming mountain of restrictions to something you can follow easily and with pleasure while your digestive symptoms diminish (or even completely resolve). Whether you need quick and easy meals to prepare or you enjoy the art of cooking a dinner-party-worthy dish, this book will guide you step by step." -- Provided by publisher.